Latin American capital flows : living with volatility, a study group report - Group of Thirty (Washington, D.C. : Group of Thirty, 1994)
"Examines capital flows to Latin America during 1980s-90s, discussing reasons for such flows and their impact on the region. Major emphasis on policy and structural reforms that must be implemented to increase capital flows"--Handbook of Latin American Studies, v. 57.
Includes bibliographical references (p. 47-49 (3rd set)).
rpm 26/08/16
Loans
Keywords: Capital movements; Capital flows; Volatility